Metastasis-directed therapy in oligometastatic prostate cancer - Miszczyk, Marcin; Soeterik, Timo; Marra, Giancarlo; Matsukawa, Akihiro; Shariat, Shahrokh F (Current opinion in urology, 2024)
PURPOSE OF REVIEW: To summarize the recent findings on the subject of metastasis-directed therapy (MDT) in the treatment of oligometastatic prostate cancer (omPCa). RECENT FINDINGS: Evidence from two randomized clinical trials (RCTs) and a meta-analysis show favorable toxicity profiles, and the potential to delay androgen-deprivation therapy (ADT) for up to two years in nearly half of patients with metachronous hormone-sensitive omPCa. Another RCT showed promising results of MDT as treatment-escalation method combined with androgen receptor signaling inhibitors (ARSI) in first-line treatment for castration-resistant omPCa.Surveys by radiation oncologists and consensus guidelines advocate for MDT across various omPCa scenarios. Multiple single-arm trials present encouraging results; however, the evidence for the benefit of MDT is still weak requiring further investigation to assess its impact on pivotal endpoints, such as survival and quality of life. SUMMARY: MDT is a promising approach in omPCa, and can be used to defer ADT in newly diagnosed metachronous omPCa patients, or to add to ARSI treatment at first diagnosis of castration-resistance. Ongoing prospective trials are needed to guide its optimal utilization in other settings, and patients should be informed about the evolving landscape of systemic therapies with proven survival benefits alongside MDT options.
Keywords: Prostatic Neoplasms; Antineoplastic Agents, Hormonal; nádory prostaty; Androgen Antagonists; Humans; hormonální protinádorové látky; mužské pohlaví; Male; lidé; antagonisté androgenů